PENERAPAN ALGORITMA C4.5 UNTUK MEMPREDIKSI PROFIT PENJUALAN - Calvin; Harman, Rika (Computer Science and Industrial Engineering, 2022)
The development of technology and information has changed all fields, including the development of the business world. It's hard to deny that today's rapidly evolving technology is attracting the attention of many people, including online marketers. An online store business needs to calculate all the important information to run the business plan they manage every year. Yanyan Boutique is a store engaged in online sales or an online store that provides products such as men's and women's clothing, men's and women's wallets, men's and women's bags. Yanyan Boutique started operating in 2018 and is located at the Pasir Putih kiosk block A no 20, Batam Center, Batam City, Riau Islands. Due to changes in customs regulations affecting shipments, every shipment from Batam is subject to heavy taxation, This results in a huge drop in sales. To perform this analysis, the researcher uses data mining techniques with the classification of the C4.5 algorithm which is carried out using manual calculations and the researcher uses the WEKA 3.9.5 application to find out the prediction results of sales profit at Yanyan Boutique. Researchers used 2 decision variables, namely Buy and Not Buy.